The effect of resources & capabilities on firm performance from the perspective of RBV - A systematic literature review - ADILA , Nadia; BOUMEDJANE , Adel (Dirassat Journal Economic Issue, 2025)
Through a systematic literature review, this paper aims to explore resources and capabilities’ effects on firm performance from a resource-based perspective and build a bridge with related core publications. A total of 59 publications were published during the period (2006-2019), in peer-reviewed journals from the Web of Science are descriptively analyzed. The key findings indicate that resources and capabilities positively affect the firm’s performance. Based on the RBV, firm performance is enhanced by optimizing internal resources and capabilities, improving business processes, generating value through efficient resource management, and achieving strategic agility.